AI Literacy Meets Ethics: Critical Appraisal's Mediating Role in Shaping Ethical Awareness in Higher Education - Pramudya Asoka Syukur; M. Miftach Fakhri; Firdaus Firdaus; Kurnia Prima Putra; Fhatiah Adiba; Fitria Arifiyanti (CV FOUNDAE, 2025)
As artificial intelligence increasingly permeates higher education systems worldwide, developing students' ethical awareness has become essential for responsible AI implementation. This study seeks to examine the connections between technical understanding, applied knowledge, and critical appraisal in shaping ethical awareness within the context of AI literacy. The study utilizes a quantitative method, applying Partial Least Squares Structural Equation Modeling (PLS-SEM) to data gathered from 322 university students. The findings indicate that technical understanding has a direct favorable influence of 0.180 on ethical awareness, while applied knowledge demonstrates a stronger impact of 0.467. Critical appraisal serves as a significant complementary partial mediator, with indirect path coefficients of 0.083 for technical understanding and 0.155 for applied knowledge, strengthening their relationships with ethical awareness. This study concludes that AI literacy educational programs should not only emphasize technical and applied knowledge but also foster critical appraisal skills to promote ethical AI usage.